Purification and Characterization of ?-1,3-Glucanase from the Antagonistic Fungus Trichoderma reesei - SRI WAHYUNI BUDIARTI; SITI MUSLIMAH WIDYASTUTI; SEBASTIAN MARGINO (Bogor Agricultural University, Indonesia, 2009)
Trichoderma enzymes that inhibit fungal cell walls have been suggested to play an important role in mycoparasitic action against fungal root rot pathogen Ganoderma philippii. This experiment was aimed to purify and characterize the ?-1,3-glucanase of T. reesei. Extracellular ?-1,3-glucanase was produced by growing mycoparasite T. reesei isolate T13 in colloidal chitin and sucrose as carbon sources. The enzyme was then purified to its homogeneity by precipitation with ammonium sulfate, followed by gel filtration chromatography and chromatofocusing. Sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE) 12% was used to confirm the purity of enzyme at each stage of preparation and to characterize purified protein. The results showed that T. reesei produced at least three extracellular ?-1,3-glucanases. Estimation of molecular weight based on SDS-PAGE 12% have three isoform of ?-1,3-glucanase were 90 kDa for ?-1,3-glucanase-I, 75 kDa for ?-1,3-glucanase-II, and 64 kDa for ?-1,3-glucanase-III. Their optimum pH and temperature were 5 and 50 oC, respectively. Key words: ?-1,3-glucanase, Trichoderma reesei, Ganoderma philippii